Frank-ter Haar syndrome associated with sagittal craniosynostosis and raised intracranial pressure - Bendon Charlotte L; Fenwick Aimée L; Hurst Jane A; Nürnberg Gudrun; Nürnberg Peter; Wall Steven A; Wilkie Andrew OM; Johnson David (BMC, 2012)
Abstract Background Frank-ter Haar syndrome is a rare disorder associated with skeletal, cardiac, ocular and craniofacial features including hypertelorism and brachycephaly. The most common underlying genetic defect in Frank-ter Haar syndrome appears to be a mutation in the SH3PXD2B gene on chromosome 5q35.1. Craniosynostosis, or premature fusion of the calvarial sutures, has not previously been described in Frank-ter Haar syndrome. Case presentation We present a family of three affected siblings born to consanguineous parents with clinical features in keeping with a diagnosis of Frank-ter Haar syndrome. All three siblings have a novel mutation caused by the deletion of exon 13 of the SH3PXD2B gene. Two of the three siblings also have non-scaphocephalic sagittal synostosis associated with raised intracranial pressure. Conclusion The clinical features of craniosynostosis and raised intracranial pressure in this family with a confirmed diagnosis of Frank-ter Haar syndrome expand the clinical spectrum of the disease. The abnormal cranial proportions in a mouse model of the disease suggests that the association is not coincidental. The possibility of craniosynostosis should be considered in individuals with a suspected diagnosis of Frank-ter Haar syndrome.